Payments for ecosystem services: a new way of conserving biodiversity in forests - Wunder, Sven; Wertz-Kanounnikoff, Shiela (2009)
The concept of payments for ecosystem services (PES) is probably the most promising innovation in conservation since Rio 1992, slowly but certainly to expand in the tropics. In a global context of stagnating or even decreasing public funding for biodiversity conservation, PES have the potential both to raise some new funds, and to absorb more efficiently money previously spent otherwise. The most novel and persuasive feature of PES lies in its “businesslike” conditional payment form, which differs from traditional conservation projects. The most promising entry point for international PES transfers for biodiversity interests seems to be to piggyback on the currently revived debate on reducing emissions from deforestation and degradation (REDD). The novel idea here would be to make agreements at the nation-state level, either bilaterally or multilaterally, and either within or outside the Kyoto framework. However, to take advantage of this opportunity, biodiversity conservation and forest stakeholders would need to be more proactive in the REDD debate than we have seen so far.